Volleyball setting skills (second contact) trainings with practice targets - Losev, A. V.; Losev, V. Y. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to analyze benefits of special practice target for the overhand/ underhand setting skills training by non-setter players.